ANALISIS DESKRIPTIF TRANSAKSI MURABAHAH PADA PT BPRS BUMI RINJANI KEPANJEN DENGAN METODE DISCLOSURE INDEX - Ningsih, Wigiati (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
Accounting treatment for shariah banking is different with accounting for conventional banking. The disclosure of financial report needs to be done to give more information for financial report users, so that the information is the important part in financial report. The purpose of this research was to analyze about the disclosure of murababah transaction in PT BPRS Bumi Rinjani Kepanjen. It used qualitative model and descriptive approach. The method which used as analysis was disclosure index. By comparing the number of items which had been stated with the items needed to be stated. The object was murababah transaction on PT BPRS Bumi Rinjani Kepanjen, and using 2012 financial report data. The result of check list number calculation in disclosure index table showed that point stated by the company were 40 points from stating 60 index points, so there were still 20 items which had not been stated. From the comparison between the item number stated all, they produced disclosure index number about 66,67%. This showed that the degree of disclosure done by company was complete. Hopefully the company is able to increase the completeness of disclosure, to give more information can influence the decision making.